SYNTHESIS AND SPECTROSCOPIC INVESTIGATIONS OF A NEW γ-L-GLUTAMYL AMIDE AS POTENTIAL LIGAND FOR TRANSITION METAL COMPLEXES - SACALIS, Carmen; HATAGAN, Maria; GAL, Emese (Studia Universitatis Babeș-Bolyai Chemia, 2025)
Considering the important chemical and biochemical application of L-glutamyl amides, this research reports a new compound namely (S)-2-amino-5-((4-(octyloxy)phenyl)amino)-5-oxopentanoic acid, as a potential ligand for transition metal complexes or for biological tests. This derivative was synthesized by a regioselective acylation of 4-(octyloxy)aniline using N-phthaloyl-L-glutamic anhydride, followed by hydrolysis of phthaloyl group with hydrazine hydrate. The mild conditions under which the reactions took place prevented the final synthetic product from being racemized. The identity of the glutamyl amide as well as the synthesis intermediates have been confirmed by spectral analyses such as 1H-NMR, 13C-NMR, HRMS and FT-IR in the solid state.